Impact of student Trust, and Positive Word of Mouth, as Mediator variables, between the dimensions of the Quality of E-learning and Student Satisfaction at King Khalid University - Alshaebi, Mohammed Alsagheer Qasem; Attico, Yasir Tageldin Abubaker (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aims to test the overall satisfaction of the beneficiary students with the quality of e-learning service at King Khalid University in the Kingdom of Saudi Arabia. More specifically, this study investigates "the effect of the variables of an e-learning service quality dimensions, which include six dimensions on an overall students’ satisfaction variable as a dependent variable, in addition to the two variables of student trust, and Positive Word of Mouth, which were used as mediator variables. The descriptive and analytical approach was used in this study, and a total of 729 copies of a questionnaire were obtained for the analyses which was representing the study population that consisted of all students at King Khalid University. So, this study tested the relationships between the variables, in purpose of testing the quality of measurements, as well as the study hypotheses testing. The results obtained from the analysis provided support for the theoretical model of the study, and confirmed the existence of a statistically significant impact relationship between the most variables, as well as The results showed that the positive word of mouth variable also mediates the relationship between students’ trust and their overall satisfaction with the e-learning service at King Khalid University. Based on the results of the study, the theoretical and practical implications of the results of the study were discussed, in addition to providing recommendations and suggestions for future studies.